LGBTQ bullying: a qualitative investigation of student and school health professional perspectives - Earnshaw, V. A.; Menino, D. D.; Sava, L. M.; Perrotti, J.; Barnes, T. N.; Humphrey, D. L.; Reisner, S. L. (Journal of LGBT youth, 2020)
Researchers and practitioners have recently called for greater involvement of school health professionals (SHPs; e.g., school psychologists, nurses, guidance counselors) in interventions to identify and address bullying of lesbian, gay, bisexual, transgender, and queer/questioning (LGBTQ) students. To inform future interventions, this study explored the perspectives of LGBTQ students and SHPs on LGBTQ bullying and SHPs' responses to LGBTQ bullying. Five online, asynchronous focus groups were held in 2018 with 28 LGBTQ students and 19 SHPs recruited from Massachusetts, US. Methods were guided by Rapid Qualitative Inquiry. Results revealed a disconnect in perceptions of LGBTQ bullying among LGBTQ students versus SHPs, with LGBTQ students reporting a range of often significant verbal, social, and physical bullying experiences and SHPs reporting minimal awareness of LGBTQ bullying at their schools. Transgender students reported bullying related to their gender identity, including verbal, physical, and sexual harassment, deadnaming (referred to by their birth name), and misgendering (called an incorrect pronoun). LGBTQ students of color reported bullying based on their race/ethnicity and pronounced social isolation. LGBTQ students reported mixed experiences with reporting bullying to SHPs. Intervention efforts are needed to enhance communication between LGBTQ students and SHPs, and to strengthen SHPs' skills to respond to LGBTQ bullying.